Does MPTP intoxication in mice induce metabolite changes in the nucleus accumbens? A 1H nuclear MRS study. (12th October 2012) - Chassain, Carine; Bielicki, Guy; Carcenac, Carole; Ronsin, Anne‐Claire; Renou, Jean‐Pierre; Savasta, Marc; Durif, Franck
<x xml:space="preserve">Abstract</x> Using in vivo1H NMR spectroscopy in a mouse model of Parkinson's disease, we previously showed that glutamate concentrations in the dorsal striatum were highest after dopamine denervation associated with an increase in gamma‐aminobutyric acid (GABA) and (Gln) glutamine levels. The aim of this study was to determine whether the changes previously observed in the motor part of the striatum were reproduced in a ventral part of the striatum, the nucleus accumbens (NAc). This study was carried out on controls and 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP)‐intoxicated mice. In vivo spectra were acquired for a voxel (8 μL) in the dorsal striatum, and in the NAc (1.56 μL). NMR acquisitions were first performed 10 days after the last MPTP injection in a basal condition [after saline intraperitoneal (i.p.) injection] and then in the same animal the week after basal NMR acquisitions, after acute levodopa administration (200 mg kg–1, i.p.). Immunohistochemistry was used to determine the levels of (Glu) glutamate, glutamine synthetase (GS) and glutamic acid decarboxylase (GAD) isoform 67 in these two structures. The Glu, Gln and GABA concentrations obtained in the basal state were higher in the NAc of MPTP‐intoxicated mice which have the higher dopamine denervation in the ventral tegmental area (VTA) and in the dorsal striatum. Levodopa decreased the levels of these metabolites in MPTP‐intoxicated mice to levels similar to those in controls. In parallel, immunohistochemical staining showed that glutamate, GS and GAD67 immunoreactivity increased in the dorsal striatum of MPTP‐intoxicated mice and in the NAc for animals with a severe dopamine denervation in VTA. These findings strongly supported a hyperactivity of the glutamatergic cortico‐striatal pathway and changes in glial activity when the dopaminergic denervation in the VTA and substantia nigra pars compacta (SNc) was severe. Copyright © 2012 John Wiley & Sons, Ltd.